Efficient induction of adventitious shoots in cotyledons of Pinus maximartinezii Rzedowski - Robledo Paz, Alejandrina; Villalobos Arámbula, Víctor Manuel; Santacruz Varela, Amalio (Instituto de Ecología, A.C., 2009)
Pinus maximartinezii Rzedowski is a nut pine native to Mexico that currently is considered as an endangered species because of disturbance of populations and natural habitat, as well as its limited geographic distribution. Even though such technologies as tissue culture could represent an alternative for its conservation and propagation, the existing literature for this pine is scarce. In this paper a protocol that allows an efficient differentiation of adventitious shoots for this species is presented. Different types of explants (embryos and cotyledons) were evaluated regarding their capacity to differentiate adventitious shoots. Explants from cotyledons showed the best response, so they were cultivated in a modified Schenk and Hildebrandt (SH) medium supplemented with four different concentrations (2.2-16.8 mg L-1) of N6-benzyladenine (BA). Percentages of explants forming shoots and number of shoots developed per explant were statistically different among the tested concentrations. The 16.8 mg L-1 of BA concentration induced the largest percentage of explants forming shoots (53.5) and the highest number of shoots developed per explant (29.1) after 14 weeks of culture. Three percent of the individual shoots produced roots. The developed methodology allows differentiation of adventitious shoots of Pinus maximartinezii from cotyledon explants, with a multiplication rate significantly higher than the one obtained by other authors.